Analisis kohesi dalam ruangan pojok / Tengku Shahrolnizam Tengku Yahya - Tengku Shahrolnizam , Tengku Yahya (2018)
The research is related to the cohesion aspects consisted in discourse analysis field. The function of the cohesion aspect is to connect an idea with another idea properly, making the text cohesive and easily understood by readers. Hence, the cohesion aspect is essential in the newspaper which is a medium of mass communication. An effective delivery of a message, especially in the editor’s view column, is essential to get the intended message across to the viewers. This research applies the theory that was forwarded by Halliday and Hasan (1976) which encompasses the textual component through grammatical device and vocabulary device. This research analyses 10 articles of the editor’s view by Awang Selamat published in Mingguan Malaysia from 18th September until 13th November 2016. The main objectives of this research are to identify the aspect of cohesion in the editor’s view column, to categorise the types of cohesion in the editor’s view column and to analyse the function of cohesion in the editor’s view column. The result of this research showed four aspects of grammatical cohesion in the data which are reference, substitution, ellipsis and conjunction. These aspects function to link the idea in the text to create meaningful phrases which can be understood by the readers. Meanwhile, two aspects of lexical cohesion which involve reiteration and collocation lexical exist to play an important role in creating significant meaning and structured data. The ability of the writer of the editor’s view column to apply both cohesion aspects makes Awang Selamat’s articles easily understandable and interesting to read. Hopefully, the research of cohesion aspects can be a guideline to language researchers to understand the aspect of cohesion in depth. In addition, it is hoped that this research can enrich prior researchers related to the cohesion aspects, thus contributing to the development of the Malay discourse field.